INFLUANCE OF TRAINING PROCESS ON DEVELOPMENT OF EXSPLOSIVE STRENGHT OF LEGS AT PIONEER BASKETBALL PLAYERS - Vukašin Badža; Dalibor Sudar (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The research is trying to give an answer on a question whether the training process which lasted two years influenced on development of exsplosive strenght of legs (one of basic psysical abilities) at pioneer basketball players. The sample in a research are basketball players from "Danubius - Vojvodina Srbijagas" team, from Novi Sad. The group counts 20 players who participated in training process and on who measuring was conducted. Data were collected per two years, and measuring were exert three times during this period. Tests that were used in this research are: long jump, high jump and running 20m. The obtained data will be processed statistically, using ANOVA for repeated measures and descriptive statistics. Research results will be represented in tables and discussed in text.